Four a Divergent collection - Roth, Veronica (New York, NY Katherine Tegen Books, an imprint of HarperCollins Publishers, 2014)
A collection of four pre-Divergent stories plus three additional scenes from Divergent, all told from Tobias's point of view, that follow Tobias's transfer from Abnegation to Dauntless, his Dauntless initiation, the first clues that a foul plan is brewing in the leadership of two factions, and the weeks after he meets Tris Prior
The transfer -- The initiate -- The son -- The traitor -- 'First jumper-- Tris!" -- "Careful, Tris" -- "You look good, Tris."
1
NEW, LITERATURE
Keywords: Courage -- Fiction; Courage; Dystopias -- Fiction; Dystopias; Identity (Philosophical concept); Identity (Philosophical concept) -- Fiction; Science fiction; Science fiction; Social classes -- Fiction; Social classes; Courage -- Fiction; Identity -- Fiction; Science fiction; Social classes -- Fiction; Fiction; Young adult fiction